(untitled) (World Bulletin of Education and Learning, 2026)
This article examines the distinctive features of football technique and the methodological foundations for developing technical skills in young players. The study emphasizes that football technique differs from many other sports because most technical actions are performed with the feet, which creates specific difficulties during the initial stages of learning. Particular attention is given to the relationship between technical mastery and physical qualities such as strength, speed, endurance, agility, flexibility, and coordination. The article highlights that effective technical performance cannot be achieved without sufficient physical and psychological readiness. It also explains the importance of age-related development, noting that the conscious teaching of football technique is most appropriate for children aged 9–11, while younger children should primarily become familiar with the ball through games and playful activities. The article discusses methodological principles such as moving from simple to complex exercises, using both whole and part-by-part teaching methods, correcting technical errors in a timely manner, and applying subjective and objective assessment tools. Special attention is paid to the role of coaches in organizing systematic training, monitoring progress, and developing players’ ability to perform technical actions under changing game conditions and opponent resistance. The article concludes that the successful formation of football technique depends on the integration of motor skill development, physical preparation, psychological maturity, methodological consistency, and continuous pedagogical control.